2004
DOI: 10.1111/j.1365-2672.2003.02168.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of creosote-contaminated soil in South Africa by landfarming

Abstract: Aims: To determine the combined effects of biostimulation and bioaugmentation in the landfarming of a mispah form (lithosol; food and Agriculture Organisation (FAO)) soil contaminated with >310 000 mg kg )1 creosote with a view to developing a bioremediation technology for soils heavily contaminated with creosote. Methods and Results: The excavated soil was mixed with 2500 kg ha )1 dolomitic lime and 2000 kg ha )1 monoammonium phosphate (MAP) before spreading over a treatment bed of shale reinforced with clay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
3
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
2
24
3
3
Order By: Relevance
“…Benzo-(a)pyrene and benzo(bϩk)fluoranthene were not significantly degraded (P Ͼ 0.05). The percentages of PAH biodegradation and the kinetics are similar to those reported in other studies (7,12).…”
Section: Resultssupporting
confidence: 79%
“…Benzo-(a)pyrene and benzo(bϩk)fluoranthene were not significantly degraded (P Ͼ 0.05). The percentages of PAH biodegradation and the kinetics are similar to those reported in other studies (7,12).…”
Section: Resultssupporting
confidence: 79%
“…This can also be attributed to the available carbon and nutrients provided by the compost system as well as the initial large population of microorganisms. Compost systems have been reported to enhance the degradation of a number xenobiotic compounds including hydrocarbon compounds (Giles et al, 2001;Atagana, 2003). However the reduction of TPH by compost organisms at the levels used in this experiment is remarkable and worth investigating further.…”
Section: Resultsmentioning
confidence: 88%
“…Aliquots (0.1 ml) of each of the dilutions 10 -6 to 10 -8 were inoculated onto mineral salts agar (MSA) plates overlaid with 50 µL of oil filter-sterilised through 0.2 µm Millipore filter membrane and incubated for 21-28 days at 28°C and checked daily for bacteria growth to avoid overcrowding of the plates. The enrichment and isolation procedures were adapted from Atagana (2003) and Mashreghi and Marialigeti (2005). Distinct colonies from the MSA plates were inoculated onto nutrient agar plates and incubated for three days at 28°C.…”
Section: Isolation and Characterisation Of Microorganisms From Compostmentioning
confidence: 99%
See 1 more Smart Citation
“…These high levels of PAHs provided a good opportunity to study and further understand the potentials of composting in soil bioremediation. Earlier, studies (Atagana 2003(Atagana , 2004 showed that higher molecular weight PAHs remained in the soil at the end of 16 weeks and 11 months of pilot-and full-scale landfarming, respectively. This study intends to exploit the high temperatures prevalent during composting, the high nutrient contents of poultry manure and the heavy microbial load of the compost system in enhancing the biodegradation of high molecular weight PAHs in the soil system under investigation.…”
Section: Introductionmentioning
confidence: 99%